The issue of interactional hypothesis: A proposal of self-determination index - Martín-Albo, José; González-Cutre, David; Núñez, Juan L. (Anales de Psicología / Annals of Psychology, 2013)
The self-determination theory (SDT) is a theory of human motivation whose postulates support the so-called interactional hypothesis, according to which intrinsic and extrinsic motivation are not independent constructs, and it also supports a simplex model of the continuum of self-determination. To test this hypothesis, a measure of self-determination, called the self-determination index (SDI) is frequently used. However, the literature reveals evident problems in the use of this index. Therefore, the aim of this research is to propose a new way of calculating the SDI from two studies, using a sample of athletes. Cluster analysis carried out in Study 1 revealed two motivational profiles, and the correlations indicated that new SDI fit the hypotheses derived from the SDT better than did classic SDI. In Study 2, results confirmed the existence of a self-determined continuum, thus supporting the interactional hypothesis as well as the relations proposed from the theory. Finally, new SDI fits the postulates of the SDT better than classic SDI, and results obtained provide preliminary support to new SDI proposed.